Orthodontic management of an impacted maxillary incisor due to odontoma - Baldawa, Rahul S. (Medknow Publications Pvt Ltd, 2011)
Odontomas are a heterogeneous group of jaw bone lesions, classified as odontogenic tumors which usually include well-diversified dental tissues. Odontomas are the most common type of odontogenic tumors and generally they are asymptomatic. Two types of odontomas are described: compound and complex based on either the appearance of well-organized tooth-like structures (compound odontomas) or on a mass of disorganized odontogenic tissues (complex odontomas). Compound odontomas have a predilection for the anterior maxilla, whereas complex odontomas have a predilection for the posterior mandible. Odontomas frequently interfere with eruption of teeth leading to their impaction. This is a case report of a 14-year-old girl with an unerupted maxillary right central incisor due to a complex composite odontoma a rare occurrence in anterior maxilla. Surgical excision of the odontoma and orthodontic treatment to get the impacted maxillary right central incisor into alignment is discussed.